A Novel Approach to Store an Image in QR Code - Nuchu Yeswanth Surya Srikar, Narisetty Srinivasa Rao, Pothana Vamsi Naidu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Quick Response Code is a machine-readable, two-dimensional barcode consisting of an array of black and white squares which can be scan quickly by any smartphone. It allows encoding over 4000 pulse characters in a two-dimensional barcode. It is used to store a small amount of information like web URL, item data, phone numbers and multimedia data. Due to restricted size in it, QR codes are presently limited in the extent to store the data. But the data in image format uses more space, if you want to store image data in QR code you must enlarge the storage capacity of QR code. In this paper, we propose a very simple form of lossy data compression, in which runs of data is dividing into blocks of equals size. The entire block is stored as a character rather than as the original run with generic HashMap which makes more robust and provides all sorts of security. Finally, our results are compared with other techniques to differentiate the optimality, efficiency of the new technique for producing optimal QR codes.